PENYALAHGUNAAN KEWENANGAN JABATAN NOTARIS ATAS PELEPASAN HAK ATAS TANAH UNTUK PENGADAAN TANAH PEMERINTAH DIKAITKAN DENGAN TINDAK PIDANA KORUPSI - Rachmawati; Maryano; Wira Franciska; Rachmawati Rachmawati; Maryano Maryano (Journal of Innovation Research and Knowledge, 2026)
The role of a Notary basically is not only to express the will of the parties in an authentic deed, but also to provide legal opinions for the parties, in order to prevent conflicts or disputes from occurring in the future. Notaries in carrying out their positions cannot commit arbitrary acts, because the Notary's actions are limited by the Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to the Law of the Republic of Indonesia Number 30 of 2004 concerning the Position of Notary (hereinafter referred to as "UUJNP ”), the code of ethics for the Notary's position, as well as other applicable regulations. The legal theory used in this study is the Theory of Legal Consequences and the Theory of Authority. The method used in this research is normative juridical research, namely library law research or secondary data with sources of primary, secondary and tertiary legal materials. The research approach used is the Statutory Approach, Conceptual Approach, Analytical Approach, Case Approach and legal material collection techniques by identifying and inventorying positive legal rules, literature books, journals and other sources of legal materials. For legal material analysis techniques, it is carried out using grammatical interpretation, historical interpretation and systematic interpretation, and legal construction methods. From the results of research on the legal consequences of abuse of the authority of a Notary in land acquisition associated with criminal acts of corruption that Notaries are subject to Article 55 of the Criminal Code, this is an alternative element, namely it is enough to prove one of the elements of the Article (person who did, ordered to do, or participated in doing). in accordance with the capacity of the actions committed by the Defendant in this case can be convicted as a criminal offender. The said deed or letter is generally entitled Deed of Relinquishment of Rights (APH). APH is sometimes also known as a Letter of Release of Rights (SPH). APH must be made before a Notary so that the strength of proof is perfect compared to if it was made privately. APH is not made by the Land Deed Making Officer (PPAT) as is the case with authentic deeds which are the authority of the PPAT as stated in Article 2 paragraph 2 of Government Regulation Number 37 of 1998 concerning Land Deed Making Officials.